2018
DOI: 10.1088/1742-6596/1054/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of critical current densities in Ba1−x K x Fe2As2 and Ba(Fe1−x Co x )2As2 with splayed columnar defects

Abstract: Abstract. Effects of bimodal splayed columnar defects in Ba 1−xKxFe2As2 and Ba(Fe1−xCox)2As2 single crystals through 2.6 GeV U irradiation and 220 MeV Au irradiation are investigated. Magnetic field profiles measured by magneto-optical imaging clarified the presence of in-plane anisotropy of the critical current density (Jc) in 2.6 GeV U irradiated crystals, where Jc parallel to the splay plane is larger than that perpendicular to the splay plane. However, the in-plane anisotropy of Jc is absent in 220MeV Au i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…The crystals were shaped into rectangular parallelepipeds with lengths and widths ~500 μm and thicknesses less than 20 μm, which is small enough compared with the projected range of 2.6 GeV U ions (65 μm). we have confirmed that the introduced CDs are continuous and their density is nearly the same as the dose of injected 2.6 GeV U ions by the STEM observation [27]. It has also been reported that the diameter of CDs generated by 2.6 GeV U ions is 7~8 nm [27].…”
Section: Methodssupporting
confidence: 81%
See 3 more Smart Citations
“…The crystals were shaped into rectangular parallelepipeds with lengths and widths ~500 μm and thicknesses less than 20 μm, which is small enough compared with the projected range of 2.6 GeV U ions (65 μm). we have confirmed that the introduced CDs are continuous and their density is nearly the same as the dose of injected 2.6 GeV U ions by the STEM observation [27]. It has also been reported that the diameter of CDs generated by 2.6 GeV U ions is 7~8 nm [27].…”
Section: Methodssupporting
confidence: 81%
“…we have confirmed that the introduced CDs are continuous and their density is nearly the same as the dose of injected 2.6 GeV U ions by the STEM observation [27]. It has also been reported that the diameter of CDs generated by 2.6 GeV U ions is 7~8 nm [27]. In addition, the variation of the diameter of CDs through the samples is negligible, since the sample is much thinner than the projection range of 2.6 GeV U ions.…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…Second, the vortex dynamics of the pristine and 3 MeV proton irradiated crystals are discussed based on magnetization measurements and analyses of magnetic relaxation. [20,23,39].…”
Section: Resultsmentioning
confidence: 99%